Multiplication of Mycobacterium tuberculosis in Peripheral Blood of Mice and Effect of Anti-tubercular Drugs on Bacteremia - Dwivedi, Richa; Singh, Shubhra; Trivedi, Priyanka; Chaturvedi, Vinita (Letters in Drug Design & Discovery, 2017)
Background: Preclinical therapeutic efficacy of new anti-TB molecules is normally assessed by examining reduction in the bacterial load in different organs of mice infected with M. tuberculosis. However, since infection in the peripheral blood can mirror overall bacillary load in the body, assessment of bacteremia may reflect the treatment outcome in a more reliable manner while obviating the need to examine different organs. Objective: This study was aimed at determining the effect of anti-TB drugs on bacteremia in mice infected with M. tuberculosis. Methods: BALB/c mice were intravenously infected with M. tuberculosis and effect of oral treatment with Isoniazid (INH) and Rifampicin (RFM) on bacilli present in the peripheral blood, lungs, spleen and liver was determined. Colony forming units (CFUs) were enumerated by plating the lysed blood sediments or tissue homogenates, onto Middlebrook 7H11 agar. Drug efficacy was assessed as log reduction in CFUs in different tissues. Results: A progressive increase in M. tuberculosis CFUs was seen in the blood of untreated mice. Upon treatment with INH and RFM, respectively, 1.77 and 1.97 log reductions in blood CFUs were seen. Multiplication and killing (after drug treatment) of M. tuberculosis in the blood and other tissues of mice were comparable. Conclusion: Determination of M. tuberculosis CFUs in the blood of mice can serve as a simple and efficient method for primary selection of in vivo active molecules.
Keywords: BALB/c mouse